The time course of reading processes in children with and without dyslexia: an ERP study - Hasko, Sandra; Groth, Katarina; Bruder, Jennifer; Bartling, Jürgen; Schulte-Körne, Gerd (Frontiers in Human Neuroscience, 2013)
The main diagnostic criterion for developmental dyslexia (DD) in transparent orthographies is a remarkable reading speed deficit, which is often accompanied by spelling difficulties. These deficits have been traced back to both deficits in orthographic and phonological processing. For a better understanding of the reading speed deficit in DD it is necessary to clarify which processing steps are degraded in children with DD during reading. In order to address this question the present study used EEG to investigate three reading related ERPs: the N170, N400 and LPC. Twenty-nine children without DD and 52 children with DD performed a phonological lexical decision (PLD) – task, which tapped both orthographic and phonological processing. Children were presented with words, pseudohomophones, pseudowords and false fonts and had to decide whether the presented stimulus sounded like an existing German word or not. Compared to control children, children with DD showed deficits in all the investigated ERPs. Firstly, a diminished mean area under the curve for the word material - false font contrasts in the time window of the N170 was observed, indicating a reduced degree of print sensitivity; secondly, N400 amplitudes, as suggested to reflect the access to the orthographic lexicon and grapheme-phoneme conversion, were attenuated; and lastly, phonological access as indexed by the LPC was degraded in children with DD. Processing differences dependent on the linguistic material in children without DD were observed only in the LPC, suggesting that similar reading processes were adopted independent of orthographic familiarity. The results of this study suggest that effective treatment should include both orthographic and phonological training. Furthermore, more longitudinal studies utilizing the same task and stimuli are needed to clarify how these processing steps and their time course change during reading development.